A new genus and species of extinct ground shark, †Diprosopovenator hilperti, gen. et sp. nov. (Carcharhiniformes, †Pseudoscyliorhinidae, fam. nov.), from the Upper Cretaceous of Germany. Issue 2 (4th March 2019) - Stumpf, Sebastian; Scheer, Udo; Kriwet, Jürgen
ABSTRACT: We describe a new genus and species of extinct ground shark, † Diprosopovenator hilperti, gen. et sp. nov. (Elasmobranchii, Carcharhiniformes), based on a single incomplete skeleton with dentition recovered from basinal marine late Cenomanian ( Metoicoceras geslinianum ammonite zone) organic-rich deposits of northern Germany. The new carcharhiniform is characterized by a unique combination of dental morphologies, indicating close architectural resemblance to the family Scyliorhinidae (catsharks). However, the very distinct tooth root morphology readily separates the new taxon from all other scyliorhinids. The extinct Cretaceous carcharhiniform † Pseudoscyliorhinus (represented by † Ps . schwarzhansi and † Ps . reussi ) shares tooth root morphologies and vascularization patterns with † Diprosopovenator, gen. nov. We hypothesize that these two sharks form part of an extinct group of carcharhiniforms characterized by a distinct root morphology (viz., low hemiaulacorhize roots with very flat and strongly flared basal faces protruding below the crown labially and mesiodistally and with a well-developed central labiobasal notch). Consequently, we propose a new family of Late Cretaceous carcharhiniforms, †Pseudoscyliorhinidae, fam. nov., to include the new taxon, as well as † Pseudoscyliorhinus . †Pseudoscyliorhinidae, fam. nov., shows a wide European distribution during the Late Cretaceous, ranging from the early Cenomanian to the late Campanian. The longevity of Scyliorhinidae, with a fossil record extending back into the Middle Jurassic, however, remains ambiguous and unresolved; therefore, it may be best to regard the assignment of fossil taxa to Scyliorhinidae as currently uncertain pending further taxonomic work.